Cold water and elite athletes - Tipton, M. (Science + Triathlon 2015 World Conference, 2015)
Immersion in cold water can have effects that range from performance decrements to death; approximately eighty percent of triathlon deaths occur during the swim (Tipton, 2013). There are four stages of immersion associated with particular risk: i. Initial immersion; ii. Short-term immersion; iii. Long-term immersion and iv. Circum-rescue (Golden & Tipton, 2002). The first three phases can result in swimming failure due to drowning, cardiac problems, neuromuscular incapacitation (local hypothermia) or general hypothermia (Golden & Tipton, 2002; Tipton et al, 1999). Some of these problems can be mitigated by prudent preparation and event planning (Tipton & Bradford, 2014). For triathletes, a cold water swim may not only have implications for swimming performance and safety, haemodynamic shifts may have consequences for hydration, and neuromuscular cooling can have a deleterious impact on transition and cycling performance. Indeed, in poor ambient environmental conditions (cold air, wind and rain) the cooling caused by swimming may be compounded during cycling (Castellani & Tipton, 2015). The University of Portsmouth Extreme Environments Laboratory was contracted by FINA, the IOC and ITU to investigate lower water temperatures for open water swimming events, particularly elite events. Since September 2014 three studies have been undertaken: two lab studies consisting of 81 individual tests in 9 different conditions, and a field study consisting of 228 individual trials across 9 events in the UK and Canada. The initial outcomes for triathletes showed that even the most vulnerable athletes were not adversely affected by swimming for 20 minutes in 12 °C water while wearing wetsuits: some did, however, exhibited a strong cold shock response on immersion at this temperature. Without wetsuits, and in 14 °C, around half the athletes tested were unable to safely complete an Olympic distance swim, a simulated transition and a 30 minute cycle. All were able to safely complete these activities in 16 °C water. In his presentation Professor Tipton will describe this research and the background to it. He will conclude with recommendations for triathlon events that include an open water swim in cool/cold water.